Choices through the life cycle - Tan, Allen L. (Philippine Journal of Psychology, 1997)
Life is a series of choice. Continually, we are faced with decisions to be made. and ultimately, the choices and decisions we make, in turn make us, or determine the life we have. In this paper, I will present some of the research that I have done over the years which highlight some crucial choices that we face over the life cycle.